Digital Support to Multimodal Community-Based Prehabilitation: Looking for Optimization of Health Value Generation - Barberan-Garcia, Anael; Cano, Isaac; Bongers, Bart C.; Seyfried, Steffen; Ganslandt, Thomas; Herrle, Florian; Martínez-Pallí, Graciela (Frontiers in Oncology, 2021)
Multimodal prehabilitation has shown its potential for most intra-cavity surgery patients on enhancing preoperative functional capacity and postoperative outcomes of these populations. However, its large-scale implementation is limited by several constrictions, such as: i) challenges of organizational change management in collaborative care; ii) insufficient access to prehabilitation; iii) relevant percentage of program drop-outs; iv) need for a more intense program personalization; and, v) economical sustainability. Therefore, if we wish to have a significant impact at the healthcare system level, the aforementioned issues need to be solved. In that sense, the modularization of prehabilitation programs and its transferability from the hospital setting to the community would potentially provide greater accessibility and allow a better personalization of these programs and, thus, optimize healthcare value generation. A core aspect to take into account for an optimal management of the multimodal prehabilitation programs is to use proper technological tools allowing: i) customizable and interoperable integrated care pathways facilitating modularization of the service and effective engagement among stakeholders; ii) remote monitoring (i.e. physical activity, physiological signs and patient-reported outcomes and experience measures) to support patient adherence to the program and empowerment for self-management; and, iii) use of health risk assessment supporting decision making for personalized service selection. The current manuscript details a proposal to bring digital innovation to novel community-based prehabilitation programs. Moreover, this approach has the potential to be adopted by programs supporting long-term management of cancer patients, chronic patients and prevention of multimorbidity in subjects at risk.